SEVERE GINGIVAL HEMORRHAGE AS FIRST CLINICAL MANIFESTATION OF THE PRIMARY IMMUNE THROMBOCYTOPENIC PURPURA: CASE REPORT AND REVIEW OF LITERATURE - Tărniceriu Claudia Cristina; Grădinaru Irina; Hurjui Ion; Balcoș Carina; Delianu Carmen; Mitrea Mihaela; Armencia Oana Adina; Hurjui Loredana Liliana (Romanian Dental Association for Education, 2020)
Primary immune thrombocytopenic purpura (ITP) is an autoimmune bleeding disorder characterized by isolated thrombocytopenia. The characteristic clinical indicators of immune thrombocytopenic purpura include: easy bruising of the skin, petechiae, ecchymosis, epistaxis, gastrointestinal bleeding, haematuria and gums bleeding. The diagnosis and management of spontaneous gingival haemorrhage can be challenging and may require a systematic medical approach. We present the case of a patient with ITP who developed severe bleeding from gums, being the first clinical manifestation of the disease. Adequate dental treatment is the requisite in order to prevent inflammation, gingival haemorrhage and infection in ITP patients. Dentists must carefully examine the oral cavity and inter-disciplinary consultation with the haematologist contribution is essential for planning dental treatment of ITP patients and determining the severity of the disorder.